ANALYSIS OF LIBRARY ORGANIZATIONAL CAPABILITIES (Lembaga Pengembangan Kinerja Dosen, 2022)
Organizational capabilities are essential for library performance. This article aims to build and determine the organizational capabilities of the library. The research method is descriptive. Data were analyzed qualitatively. The results showed that the organizational Capability for increasing library performance was not optimal. Organizational capabilities are not by library programs, so library performance is not maximized.